Ageing in Place in Rural Areas of Western Australia: Actions, Choices and Preferences - Boldy, Duncan; Grenade, L.; Lewin, Gill; Karol, Elizabeth; Burton, Elissa (Rural Development Institute, Brandon University, 2013)
The objective of the study was to explore the moving and staying actions and intentions of older people (50+) living in rural areas of Western Australia (WA) and to compare results with those living in metropolitan Perth/Fremantle. The design involved a cross-sectional postal survey of a sample of WA members of National Seniors Australia, living in their own homes in the community, followed by in-depth interviews with a subset of survey respondents (n=39). Most survey respondents lived in metropolitan Perth/ Fremantle (1630), followed by country towns (1092) and more rural locations (291). Interviews were conducted with 39 participants, 19 of whom lived outside the metropolitan area. The main outcome measures consisted of the proportions of respondents by location and age group who had moved, were thinking of moving or were intending to stay put; also the main reasons for such actions and intentions. Rural respondents were 1.3 times more likely to be thinking of moving in the short term compared to metropolitan respondents. A key reason given for moving from rural areas was ‘thinking about where wanted to live for rest of lives’, this tending to be associated with ‘employment’ or ‘retirement’ for those under 65; with ‘retirement’, ‘closer to family/friends’ and ‘upkeep/maintenance difficulties’ being particularly important for those 65+. ‘Wanting a lifestyle change’ was a key reason for moving to a rural location for those aged under 65. The study concluded that there are a number of issues faced by older people living in rural areas of WA which limit the extent to which ‘ageing in place’ is a viable choice for them as they age.